Evaluating Students’ Learning Experiences Using Course Management System in a Blended Learning - Marva Mirabolghasemi; Noorminshah A. Iahad; Muhammad Qomaruddin (IAES Indonesia Section, 2014)
One of the major software used in today’s classroom are Course Management Systems (CMS). There is currently little research regarding the learning experience of students using CMS like Moodle in a blended learning environment. Effective learning environments give students a chance to learn better and faster. Understanding the students’ learning experience in a blended course using a CMS is the first step to determine how to best engage students. It assumes that good learning environments are achieved through three factors which are Cognitive Presence, Teaching Presence, and Social Presence. This study used a set of questionnaire to evaluate students’ learning experience for 107 students in blended learning. Correlation analysis has been used to find the relationship between Cognitive Presence, Teaching Presence, Social Presence and learning experience of students who use CMS in blended learning. The findings of this research study show that there is a significant correlation among Cognitive Presence, Teaching Presence, Social Presence and the overall learning experience using Moodle in blended learning. However, the level of Social Presence is lower in comparison with Teaching Presence and Cognitive Presence.